TINJAUAN KETIDAKLENGKAPAN PENGISIAN FORMULIR RINGKASAN MASUK DAN KELUAR REKAM MEDIS RAWAT INAP PADA PENYAKIT HIPERTENSI DI RSUD LUBUK BASUNG - Yulfa Yulia; Oktamianiza Oktamianiza; Dian Sari; Kalasta Ayunda Putri; Vitratul Ilahi; Gopinda Deska Putra (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
The admission and discharge summary is a medical record form that is used to record a summary of the course of the disease from the time the patient entered the hospital until the patient was discharged. The research used is quantitative research with a descriptive approach. Data collection was carried out at Lubuk Basung Regional Hospital from 27 May to 1 July 2023 and the sample consisted of 88 entry and discharge summary forms from the medical records of patients suffering from hypertension. Research through observation with a checklist table. Computerization is used to process data and carry out univariate analysis. The research results showed that there were still incomplete filling out of the entry and discharge summary forms on patient identification items (40.9%), important patient reports (20.5%), patient authentication (12.5%), good record keeping (15.9%). ), and scribbled and clearly legible (17.05%). The results showed that the summary form for admission and discharge for hypertensive patients was still incomplete. In conclusion, this shows that the summary form for admission and discharge for hypertensive patients is still incomplete. It is recommended to carry out evaluations and reviews, as well as outreach and evaluation with doctors, nurses and other related personnel. It mainly deals with the quantitative analysis of incoming and outgoing summary forms.